Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s13224-016-0876-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Leading to Pregnancies in Stimulated Intrauterine Insemination Cycles and the Use of Consecutive Ejaculations Within a Small Clinic Environment

Abstract: Introduction Understanding and improving IUI pregnancy rates has enormous global appeal and application. This pilot study goes one step further by utilising consecutive ejaculates from men with oligozoospermia and comparing with normozoospermic male group. Materials and Methods A retrospective analysis was performed on 117 IUI-stimulated treatment cycles in a small fertility clinic in North Middlesex University Hospitals Trust, UK, within a NHS setting. Risks of OHSS and multiple births are carefully controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In IUI or ART, for example, it could be suggested to separate spermatozoa by the swim-up of a second ejaculate, particularly if the first one results in suboptimal parameters. In fact, Bahadur and colleagues [34] showed that recurrent ejaculates successfully improved IUI pregnancy rates and that reduced male abstinence to 12-24 h was associated to improved pregnancy rate with ICSI [34]. In the latter case, after swim-up with the second consecutive semen sample, the oocyte can be injected with spermatozoa of better quality, considering the increased probability of choosing a gamete with intact DNA among the many deemed morphologically "normal" by the embryologist.…”
Section: Discussionmentioning
confidence: 99%
“…In IUI or ART, for example, it could be suggested to separate spermatozoa by the swim-up of a second ejaculate, particularly if the first one results in suboptimal parameters. In fact, Bahadur and colleagues [34] showed that recurrent ejaculates successfully improved IUI pregnancy rates and that reduced male abstinence to 12-24 h was associated to improved pregnancy rate with ICSI [34]. In the latter case, after swim-up with the second consecutive semen sample, the oocyte can be injected with spermatozoa of better quality, considering the increased probability of choosing a gamete with intact DNA among the many deemed morphologically "normal" by the embryologist.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, short-term recurrent ejaculation may be a simple noninvasive maneuver to improve SDF. Although the beneficial effect of short EA on natural conception is unclear, application of the technique to assisted reproduction may have its value [224][225][226]. In addition to higher pregnancy rates in ICSI, recurrent ejaculation has been associated with a significantly lower SDF [227] (Table 3).…”
Section: Short Ejaculatory Abstinencementioning
confidence: 99%
“…First-line treatment using IUI must be attempted in all patients except in women with cervical atresia, cervicitis, endometritis or bilateral tubal obstruction and in most cases of amenorrhoea or severe oligozoospermia. 'Consecutive ejaculate' qualities in subfertile males also support in-depth analyses of subfertile males [8].…”
Section: Introductionmentioning
confidence: 58%
“…The systematic review found no difference in the pregnancy rate per couple with two inseminations compared with one [15]. In the majority of studies, IUI is done 32-36 h following hCG administration, although in one pilot study it appears that optimal time post-hCG trigger for a pregnancy was 30 h [8]. There may also be differences in what is optimal for trigger in Clomid cycles and hMG cycles.…”
Section: Timing Of Inseminationmentioning
confidence: 96%